Peningkatan Kesadaran Anti Bullying melalui Peer Group Teknik Sosiodrama pada Siswa SMP - Syifa, Abdullah; Nugraha, Wira; Oktaviana, Sherli Kurnia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This community service aims to examine the impact of the sociodrama program in addressing bullying behavior at SMPN 1 Anjongan. The sociodrama program was implemented as a preventive and intervention effort to reduce bullying and increase students' awareness of the importance of empathy and appreciating differences. The sociodrama method was used to form anti-bullying peer groups, which serve as agents of change in creating a safe and conducive learning environment at school. This service reveals that the implementation of sociodrama significantly increases students' awareness of the impact of bullying on perpetrators, victims, and bystanders. In addition, this program has successfully formed peer groups that support prosocial behavior and address negative behavior. Other positive impacts include the creation of a more inclusive and harmonious school atmosphere, with increased solidarity among students and active participation in bullying prevention. Furthermore, teachers involved in this program have also acquired new skills in addressing bullying issues and integrating character education into daily learning. This program demonstrates that experience-based approaches such as sociodrama can be an effective method in building an anti-bullying school culture and improving the quality of character education in schools.